2018
DOI: 10.1038/s41417-018-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic response of 5-fluorouracil-resistant cells to gene- and cell-directed enzyme/prodrug treatment

Abstract: Gene-directed enzyme/prodrug therapy (GDEPT) mediated by mesenchymal stromal cells (MSC) was already approved for clinical study on a progressive disease refractory to standard therapy. In this work, we examined the effect of several GDEPT approaches on chemoresistant cells. First, we derived 5-fluorouracil (5-FU)-resistant variant of human colorectal adenocarcinoma cells HT-29 designated HT-29/EGFP/FUR. Our data show that the upregulation of thymidylate synthase (TS) and downregulation of thymidine phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This strategy involves the introduction of a sequence of genetic material in tumor cells, triggering the necessary mechanisms to activate the apoptotic pathways themselves or facilitate the activation of certain compounds that can spread to neighboring malignant cells and mediate their destruction [ 4 ]. Suicidal genes promote a cytotoxic effect after their expression in the target cell, by encoding enzymes that convert non-toxic prodrugs into highly toxic metabolites [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy involves the introduction of a sequence of genetic material in tumor cells, triggering the necessary mechanisms to activate the apoptotic pathways themselves or facilitate the activation of certain compounds that can spread to neighboring malignant cells and mediate their destruction [ 4 ]. Suicidal genes promote a cytotoxic effect after their expression in the target cell, by encoding enzymes that convert non-toxic prodrugs into highly toxic metabolites [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo , 5-FU is transformed into FU deoxynucleotide (F-duMP) via the OPRT-RR and TP-TK pathways, inhibiting thymidylate synthase (TS), preventing dUMP methylation to dTMP, inhibiting DNA synthesis, and arresting the cell cycle in the S phase ( 7 ). Several studies have reported that gene polymorphism and TS upregulation in CRC are closely related to 5-FU tolerance ( 7 , 99 , 100 ). Thymidine phosphorylase (TP) is upregulated in CRC, which has a poor prognosis.…”
Section: Tcm Reverses the Chemoresistance Of Crc And Inhibits Tumor G...mentioning
confidence: 99%
“…Polyethylenimine based polymers were used to transiently engineer MSC with HSV-TK, together with TRAIL: These modified cells were effective in vitro and in vivo against glioma through increased apoptosis and reduced angiogenesis[ 178 ]. MSC expressing CDy::UPRT by the same transfection method significantly inhibited in vivo temozolomide resistant glioma tumors[ 179 ] as well as 5-fluorouracil resistant colorectal adenocarcinoma cells[ 180 ].…”
Section: Arming Msc Toward Cancermentioning
confidence: 99%